Business in practice: how early success fosters unforeseen setbacks - Vieira, Catarina Andreia Martins Pastilha (2022)
Electrification of vehicles has gained increasing preponderance over the last few years. If, on the one hand, it denotes the urgency and attention towards a more sustainable future, for companies in the sector it means a higher volatility in terms of workflows and team management, in order to keep up with the latest technologies and to not fall short of other competitors. Throughout this project, it will be simulated a real-life scenario describing the electrification journey of a company, the most significant challenges that are faced along this path and its customized cost-leadership strategy to conquer this emerging disruption market.